TINJAUAN YURIDIS PENCEMARAN LAUT OLEH KAPAL ASING YANG DISEBABKAN OLEH TERSANGKUTNYA JANGKAR KAPAL PADA PIPA MINYAK MILIK PT PERTAMINA DI WILAYAH LAUT TERITORIAL INDONESIA - Maghfira Dwi Adisti; Zulfikar Jayakusuma; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Environmental pollution that occurred in Balikpapan Bay due to leaking oil pipes belonging to PT. Pertamina is an important case because it causes pollution of the marine ecosystem so that it disrupts environmental functions. In this case, the leakage of the oil pipe was caused by the catch of the anchor of the MV Ever Judger ship, this caused Indonesia to not be directly responsible for it, as regulated in the UUPLH due to the absence of a single factor and as well as the presence of force forward in the case of pollution in Balikpapan Bay. The single factor error referred to in the pollution case in Balikpapan Bay is that more than one party is responsible for the subject. The first party is the MV Ever Judger ship who dumped the ship in the Prohibited Restricted Area (DTT), which should not have dumped the anchor because it could disrupt pipeline operations. The second party, PT Pertamina, as the owner of the pipes, needs to be checked whether the laying of the pipelines supplied with oil has taken into account the details of the pipes even in an emergency.The purpose of the author's research is to determine the effect of international regulations regarding violations by foreign ships that cause pollution in the sovereign territory of the Republic of Indonesia and to find out the efforts of national law in resolving the problem of violations by foreign ships that cause pollution in the sovereign territory of the Republic of Indonesia.This type of research the author is a type of juridical normative research, because in this study the authors took data based on literature review. From the results of the research, the research problems that can be concluded are, first, the author's research suggests the form of responsibility in environmental pollution that cannot be found a single factor of error and involves the subject of international law. The second problem is the Indonesian government's efforts in dealing with the pollution case in Balikpapan Bay, including the provision of punishment and compensation.